KAJIAN REOLOGI BEBERAPA LEMPUNG KOMERSIAL DALAM MEDIUM AIR - Mulijani, Sri
Abstract: In the ceramic industries, understanding the physical behaviour of the processing materials is becoming of importance to accurately determine the quality of the final products. Research has been conducted to investigate the suspension flow behaviour of three types of ceramic materials (A,B and C) in water. Clay suspension in water is employed as casting slips in many ceramic industries. Following beneficiation process, the mineral composition of the three types of clays was analysed by using X-ray diffractometry, DTA, FTIR, and optical microscopy. The morphology, particle size and semiquantitative analysis of the elements were determined by using SEM-EDAX. The rheological study was carried out by measuring the variation of shear stress with respect to shear rate by using Brookfield Rheometer model DV-III. It was found that the mineral characteristics of clay A contains halloysite, and alpha quartz, clay B contains feldspar, halloysite, montmorillonite and alpha quartz, where as clay C contains kaolinitc and alpha quartz. The flow behaviour of clay A and B with 30,40 and 50% (w/v) concentrations, show a pseudoplastic type of flow behaviour at low shear rates and Newtonian at high shear rate. For clay C with 30,40, and 50% concentrations, the floww shows pseudoplastic behaviour at loww shear rate and almost follows Newtonian fluid at high shear rate.